Modelling of crystal plasticity effects on the crack initiation energies of a bi-crystal interface (Nb/ A120 3) - Siddiq, Amir; Schmauder, Siegfried (Computer Assisted Methods in Engineering and Science, 2007)
The present paper examines the crystal orientation effects on the energy at the crack-tip of niobium/ alumina joints. The analyses have been done using crystal plasticity theory. The single crystal parameters are identified for each family of slips system in [21]. These identified parameters are being used to examine the orientation effects of the niobium single crystal on the energy at the crack-tip. Differences in the fracture energy are explained based on the plastic slip (strain) induced in different slip systems during deformation. A qualitative comparison of the crystal plasticity analysis with the experiments of [4, 15] is also been presented.